Teacher's Readiness to Teach Literacy and Numeracy: A Literature Review - Wahyu Kyestiati Sumarno; Prismahardi Aji Riyantoko; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama (Future Science, 2023)
The preparedness of educators to teach foundational skills such as literacy and numeracy is critical for student success, especially in the early years of education. This literature review explores the current body of research on teacher readiness to instruct in these essential areas. Methodologically, the review synthesizes empirical studies, theoretical frameworks, and best practices published in peer-reviewed journals, reports, and educational white papers. Key findings reveal that teacher readiness is influenced by multiple factors including educational background, professional development, access to resources, and pedagogical support. The review also identifies gaps in the existing literature, particularly in the context of digital transitions and inclusive education. The insights gained from this study could guide future research and inform policy interventions aimed at enhancing teacher readiness for effective literacy and numeracy instruction.